2017
DOI: 10.1080/02670844.2017.1292706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing on Al–Si coating synthesised by mechanical alloying

Abstract: An Al-Si composite coating was synthesised on Ti-6Al-4 V alloy substrate by means of mechanical alloying. The as-synthesised coating had a composite structure. The effects of annealing treatment on the microstructure, the mechanical properties and the oxidation resistance of coating were investigated. The increase in annealing temperature was conductive to the formation of multilayered structure of the coating. The formation processes of the layers at different annealing temperatures were discussed. The coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…It is reported that the material will undergo recovery and recrystallization during the annealing process of recrystallization, 30 which is beneficial for eliminating defects such as pores and cracks. In addition, according to Chen et al, 31 heat treatment is beneficial to the densification and homogenisation of the microstructure of MA-prepared coatings, which is consistent with the results of this work. Figure 8(e)-(f) provides the EDS results of the marked area A and B in Figure 8(a).…”
Section: The Effects Of Annealing Treatment On the Microstructure Of ...supporting
confidence: 93%
“…It is reported that the material will undergo recovery and recrystallization during the annealing process of recrystallization, 30 which is beneficial for eliminating defects such as pores and cracks. In addition, according to Chen et al, 31 heat treatment is beneficial to the densification and homogenisation of the microstructure of MA-prepared coatings, which is consistent with the results of this work. Figure 8(e)-(f) provides the EDS results of the marked area A and B in Figure 8(a).…”
Section: The Effects Of Annealing Treatment On the Microstructure Of ...supporting
confidence: 93%
“…In comparison, the ultrasonic vibration-assisted cladding layer surface showed finer grooves as shown in Figure 10(c1,c2). This is because the microhardness of the cladding layer was higher and more uniform than that of the non-vibrating cladding layer, leading to the difficulty for contact region to produce plastic deformation, thus effectively protecting the substrate and improving the wear resistance of the coating [31]. The improvement in wear resistance of cladding layer assisted by ultrasonic vibration can be attributed to the fine grain strengthening caused by the synergistic effect of ultrasonic cavitation and stirring due to acoustic streaming on growing dendrites as well as the solidification microstructure growth temperature gradient and solidification rate changes.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion resistance was enhanced for the coating annealed at an optimum temperature after chloride treatment. The annealing process started the formation of dense interior microstructures with continuous oxide layers due to dehydration-assisted internal tensile stress release at 250 • C [65,66]. The passive and stable coating inhibits the electrolyte uptake towards the Mg surface and blocks the formation of cathodic sites of Mg by obstructing the diffusion pathways (figure 4).…”
Section: Corrosion Studies Of Coatingsmentioning
confidence: 99%